(3GdETGQGJ hGdJfHjgGJ aj GdefWb hGdMceIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3CMeO Gddg JYGdi agPG GdcJGH ai gPg GdETGQGJ hGdJfHjgGJ s
(3BNQgG (B:s
(3Edi GdMb HeYfi GdQVG hGdUOb aGjI eG jSdc ajg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B94s
Keywords: (3GdadSaI hGdefWbs